Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure, pricing, and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

Markets and Society - Zaman, Asad (Social Science Research Network, 2015)
In face of the strong conflict between market norms and social norms, peaceful co-existence is impossible. In traditional societies, markets were subordinated to society. Modern society emerged via a number of revolutions which made society subordinate to markets. This led to a reversal of traditional values of social cooperation and harmony with nature. Instead, men, nature, society became objects to be exploited for creating profits. A market society generates profits by exploiting men and nature, and requires increasing profits to sustain itself. This process has run into its limits as planetary resources are being destroyed on a scale large enough to threaten the planet. Saving the planet requires reversing the transition to modernity by subordinating markets to society. This is a difficult task.
Keywords: Great Transformation, The (Book); environmental economics; exploitation; market society

The meta-crisis of secular capitalism - Milbank, John; Pabst, Adrian (International Review of Economics, 2015)
The current global economic crisis concerns the way in which contemporary capitalism has turned to financialisation as a double cure for both a falling rate of profit and a deficiency of demand. Although this turning is by no means unprecedented, policies of financialisation have depressed demand (in part as a result of the long-term stagnation of average wages) while at the same time not proving adequate to restore profits and growth. This paper argues that the current crisis is less the ‘normal’ one that has to do with a constitutive need to balance growth of abstract wealth with demand for concrete commodities. Rather, it marks a meta-crisis of capitalism that is to do with the difficulties of sustaining abstract growth as such. This meta-crisis is the tendency at once to abstract from the real economy of productive activities and to reduce everything to its bare materiality. By contrast with a market economy that binds material value to symbolic meaning, a capitalist economy tends to separate matter from symbol and reduce materiality to calculable numbers representing ‘wealth’. Such a conception of wealth rests on the aggregation of abstract numbers that cuts out all the relational goods and the ‘commons’ on which shared prosperity depends.
Keywords: abstraction; financialisation; financialization; materialisation; meta-crisis

Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Hayek versus Polanyi: Espontaneidade e designio no capitalismo. (Hayek versus Polanyi: Spontaneity and Design in Capitalism. With English summary.) - de Almeida, Rafael Galvao; Garcia Fernandez, Ramon (Economica (Fluminense Federal University), 2015)
This work introduces the concept of spontaneous order, its development through many schools of economic thought and its importance to today's society. This paper gives emphasis to Friedrich Hayek, since he has the most known model of spontaneous order, how he started to elaborate from his research about the role of the information on the economy and his maturation in Law, Legislation and Liberty. As a counterpoint to the Hayekian model, this work includes criticism to the concept and the work of Karl Polanyi is analyzed. He diverged from Hayek about the role of the market in the society, when he affirmed that society protects itself from the invasion of the market in the other social spheres, through the process of double movement. Lastly, it is concluded that there is no evidence to discard the existence of spontaneous orders; the double, that double movement, because it is started with the individuals before taking legislative form, has the necessary characteristics to be considered a type of spontaneous order; and, due to the self-organizational trait of spontaneous order, there are practical problems in political anarchism.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; belief; communication; elections; history of economic thought; information and knowledge; learning; legislatures; lobbying; market structure, pricing, and design; political processes: rent-seeking, lobbying, elections, legislatures, and voting behavior; rent-seeking; spontaneous order; unawareness; voting behavior

Strengthening Karl Polanyi’s Concepts of Reciprocity, Double Movement, and Freedom with the Assistance of Abductive Logic - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
My purpose here is to strengthen Karl Polanyi’s work through critique of and extension to abductive processes. Polanyi presented history woven into a new paradigm for analysis of socioeconomic systems, demonstrated discovery similar to abductive processes, and extended abduction into a holistic context. One of Polanyi’s most important contributions to socioeconomic analysis is the explanation of three integrated network models of socioeconomic reciprocity. They are coadjuvancy, redistribution, and market exchange. Polanyi extended abductive reasoning in two ways. First, he extended it beyond the cognitive logic of a person to inferences and societal belief changes of institutions. Second, he showed that, in the real world, beliefs are not only fixed like an abductive process, they are fixed in law. Throughout Polanyi’s historical presentation, market beliefs are being revised, thus serving as a demonstration of the abductive process. I make both positive and negative critique of a number of Polanyi’s concepts, with special attention to reciprocity, the double movement, and freedom. This critique and abduction extension strengthens Polanyi’s paradigm for future socioeconomic analysis with his integrative network models.
Keywords: abductive logic; beliefs; double movement; economic theory; freedom; production; reciprocity; reciprocity (commerce); socioeconomic; socioeconomics; stock exchanges

Basic Income, Full Employment, and Social Provisioning: Some Polanyian/Keynesian Insights - Seccareccia, Mario (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
The purpose of this article is to offer a Polanyian perspective on the issue of guaranteed income (GI). In analyzing the debate over the Speenhamland system, especially as Karl Polanyi ([1944] 2001) describes it inThe Great Transformation, he offered an important criticism of a GI program that some contemporary Polanyian economists have been struggling to come to terms with in their writings. Instead of defending a GI policy by seeking to reject Polanyi’s analysis of the problem, I suggest that we should consider embracing Polanyi’s concern by proposing a comprehensive twin policy that would complement a basic income program with a Keynesian full employment commitment.
Keywords: English Poor Laws; Keynesianism; Speenhamland system; basic income; economists; full employment; full-time employment; guaranteed annual income; income; income supplementation

Provision of Social Costs and the Free Market: A Polanyian Perspective - Vidal, Gregorio; Marshall, Wesley; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
In this article, we analyze at a conceptual level some of the more relevant effects of the neoliberal takeover on the provision of social costs, including employment, health care, and nutrition. Adopting key perspectives of Karl Polanyi and other thinkers, we develop our examination under the seemingly perpetual conflict between markets and social reproduction. We argue that financialization has both expanded market spaces and changed relationships within those spaces. The ever-greater domination of financial markets means that employment has become increasingly more precarious in the strict spaces of the labor market. At the same time, financialization has steadily eroded the social forms that exist outside of formal markets, greatly weakening the mechanisms through which societies can both defend themselves from predatory markets and reproduce themselves with some degree of purpose and hope for the future.
Keywords: employment (economic theory); externalities; externalities (economics); financialization; free enterprise; neoliberalism; nutrition; social reproduction

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM -- on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

To boldly go (Fund Strategy, 2015)
The article provides the author's view on issues concerning free market economics. He mentions Mr. Spock, a fictional character in the "Star Trek," whom critics of free market economics often cite as the epitome of rational economic man or Homo Economicus, as well as features Karl Polanyi, a Hungarian-American economist, who opposed the idea of humans as rational economic agents in his work "The Great Transformation." He also mentions human reason and cultural pessimism.
Keywords: Spock, Mr.; capitalism; economists; free enterprise

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning

Critique and transformation: On the hypothetical nature of ecosystem service value and its neo-Marxist, liberal and pragmatist criticisms - Melathopoulos, Andony; Stoner, Alexander (Ecological Economics, 2015)
Ecosystem service valuation (ESV) attempts to transform the opposition of human economic necessity and ecological conservation by valuing the latter in terms of the services rendered by the former. However, despite a number of ESV-inspired sustainability initiatives since the 1990s, global ecological degradation continues to accelerate. This suggests that ESV has fallen far short of its goals of sustainable social transformation—a failure which has generated considerable criticism. This paper reviews three prominent lines of ESV criticism: 1) the neo-Marxist criticism, which emphasizes the “fictitious” character of ecosystem commodities; 2) the liberal criticism through Friedrich Hayek's concept “scientistic objectivism”; and 3) the pragmatist criticism of “value monism”. Although each form of criticism provides insight into the limitations of ESV, all share ESV's inability to discern what kind of social transformation is possible . Unable to provide an account of their own immersion in social and historical context, these approaches operate in the hypothetical . In light of these shortcomings, this paper advances a critical theory approach, which we contend provides conceptual tools uniquely well-suited to more adequately address the question of social transformation.
Keywords: Marxian economics; ecosystem services; neoliberalism; pragmatism; social development